Role of Multimedia Resources in English Language Learning: An Overview - Subramanian, Lakshmi (Integrated Journal for Research in Arts and Humanities, 2024)
The following study has been developed to understand the utility of multimedia resources in learning the English language. Multimedia resources are a combination of multiple content forms including texts, video, audio, animation and others. Successful utilization of multimedia resources can enhance the effectiveness of the entire teaching program. Secondary research has been performed to complete this study.